Genetic depletion reveals an essential role for an SR protein splicing factor in vertebrate cells. - Mount, S M (Bioessays, 1997)
SR proteins are essential for the splicing of messenger RNA precursors in vitro, where they also alter splice site selection in a concentration-dependent manner. Although experiments involving overexpression or dominant mutations have confirmed that these proteins can influence RNA processing decisions in vivo, similar results with loss-of-function mutations have been lacking. Now, a system for genetic depletion of the chicken B cell line DT40 has revealed that the SR protein ASF/SF2 (alternative splicing factor/splicing factor 2) is essential for viability in these cells(1). This study opens the way for a complete functional dissection of this protein, and other SR proteins, in vivo.
Keywords: Amino Acid Sequence; Animals; Molecular Sequence Data; Nuclear Proteins; RNA Splicing; RNA-Binding Proteins; Serine-Arginine Splicing Factors; Vertebrates